Design of a double-optimized lattice structure using the solid isotropic material with penalization method and material extrusion additive manufacturing. (September 2020) - Kim, Han-Wool; Kim, Young-Seong; Lim, Joong Yeon
The development of additive manufacturing technology has facilitated the production of cellular structures such as lattices. Topology optimization is a tool for computing the optimal geometry of an object within certain conditions, and it can be used to increase the stiffness and decrease the weight. In this study, a "double-optimized lattice structure" was designed by applying the solid isotropic material with penalization method for topology optimization twice, first to optimize the unit cell of the lattice and then to grade and insert the cells into a global model. This design was applied to a Messerschmitt–Bölkow–Blohm beam and produced via material extrusion additive manufacturing. Subsequently, it was evaluated by a three-point bending test, and the results indicated that the double-optimized lattice beam had a 1.6–1.9 fold greater effective stiffness and a 2 fold higher ultimate load than the values obtained for the beam designed with conventional methods. Thus, the double-optimized lattice structure developed herein can be an effective material with regard to its low weight and high stiffness. Contrarily, the penalty factor p of the solid isotropic material with penalization did not affect the properties. This finding suggests that p can control homogeneity while maintaining the strength of the structure.